Performance, emissions and wear characteristics of an indirect injection diesel engine using coconut oil blended fuel - Masjuki, H.H.; Kalam, Md Abul; Maleque, Md. Abdul; Kubo, Aizoh; Nonaka, Tetsuya (SAGE Publications Inc., 2001)
Dynamometer tests have been carried out to evaluate the performance, emissions and wear characteristics of an indirect injection diesel engine when fuelled by 10, 20, 30, 40 and 50 per cent blends of ordinary coconut oil (COCO) with ordinary diesel fuel (OD). The test was conducted for 100 h using each of the test fuels to monitor the eVect of COCO blends on the wear and lubricating oil performance. OD fuel was also used for comparison purposes. The operating performance of the engine and the emission characteristics of exhaust gases were compared. The eVect of blended fuel on the engine’s wear and lubrication characteristics in terms of wear metal (Fe), water concentration, oxidation, viscosity, total base number and additive depletion was analysed. The performance and emissions characteristics results showed that 10–30 per cent coconut oil blends produced slightly higher performance in terms of brake power than OD. All the COCO blends produced lower exhaust emissions including polycyclic aromatic hydrocarbons and particulate matter. The wear and lubrication oil characteristics results showed that COCO blends up to 30 per cent produced similar results to OD. This programme will give useful information for further research and development in the future if COCO is used as an alternative to OD.